Robot-assisted thoracoscopic enucleation for a large esophageal leiomyoma: a case report - Kohei Kemuriyama; Satoru Motoyama; Yusuke Sato; Akiyuki Wakita; Yushi Nagaki; Hiromu Fujita; Ryohei Sasamori; Kazuhiro Imai; Masaki Aokawa; Yoshihiro Minamiya (Surgical Case Reports)
Abstract Background Video-assisted thoracoscopic surgery (VATS) is being used to treat esophageal submucosal tumors (SMTs) all over the world. However, this technique is difficult when the tumor is large and located on the left side wall of the esophagus, within the upper mediastinum. This is because, with VATS, the surgical forceps have a limited range of motion. Robot-assisted thoracoscopic surgery (RATS) using the da Vinci surgical system may be extremely useful for enucleation of esophageal SMTs within the narrow upper mediastinum. Case presentation A female in her thirties experiencing epigastric pain visited our hospital and was diagnosed with a large esophageal leiomyoma within the upper mediastinum. From its size (10 cm), it was judged to have malignant potential. We performed SMT enucleation using RATS with a da Vinci surgical system Xi. This was our second case using this system. The patient was placed in the left lateral position. Four da Vinci trocars (8 mm) were inserted into the 10th, 7th, 5th and 3rd intercostal spaces (ICS), and an assist port was added in the 5th ICS. We opened the superior mediastinal pleura cranially and caudally from the arch of the azygos vein and expanded the superior mediastinum after dividing the azygos vein. We made an incision in the muscular layer of the esophagus and, using a monopolar hook and monopolar scissors, enucleated the esophageal tumor in a protective manner so as not to damage its capsule or mucosa while applying appropriate robot-specific counter traction. We then sewed up the muscularis using 4–0 Vicryl, inserting the endoscope into the thoracic esophagus to substitute for a bougie. In addition, the pleura was sutured using barbed suture. The surgical procedure was straightforward and smooth. The patient was discharged on postoperative day 4 with no surgical complications. The tumor was definitively diagnosed pathologically from paraffin sections as a benign esophageal leiomyoma. Conclusions RATS enables more delicate and precise esophageal SMT enucleation without surgical complications, though various challenges remain to be overcome.